(untitled) (International Journal of Geoscience, Engineering and Technology, 2020)
Paving Engineering can be responsible for a considerable part of the environmental impact on infrastructure and construction projects. As a result, sustainability once again becomes a key research theme. This article aims to raise sustainable aspects related to LCA (Life Cycle Assessment), and its use in paving with recycled materials. With the increasingly frequent use of recycled or even reused materials, it is necessary to establish methodologies to quantify the level of sustainability of a product/process. Thus, results can be obtained that go beyond the life of the pavement, allowing a better understanding of the negative impacts, such as the energy demand involved in the construction, operation, and maintenance of the track. In addition, through weightings about each impact (environmental, social, and economic) it is possible to have better decision-making, as well as better optimization of applicable resources. The LCA allows the determination of a sustainability factor, being able to consider parities in the weightings, that is, 33.33% for each assessed impact (social, environmental, and economic). Or allocate 50% for environmental impact and 25% for social and economic impacts. A consideration is possible in which 50% weighting is adopted for economic impact and 25% for social and environmental impacts. This factor allows for better decision making, allowing to assess the pillar of greatest interest.